White capitalism within communities of craftivism: mask making and health maintenance disparities during COVID-19 - Anderson, Wendy K. Z.; Davis, LaShara A. (Frontiers in Communication, 2023)
When lockdown started, my anxiety kept me on a tight string-I (author 1) remember drowning in intense, omnipresent agitation as I used every “extra” moment I could to research mask styles, adapt patterns published online or distributed by different organizations to increase access to masks for better functionality, and distribute masks to those who needed them via an old ice cream bucket on my front bench. Yet, I recognized that the time I used, my ability to quarantine and so much more contributed to my privilege in doing so. I (author 2) had no masks on hand, so after watching a few tutorials online, I concocted my own makeshift mask. Not only did my MacGyvered creation not fit properly, it was super hot and lacked sufficient air flow due to the thickness of the fabric. Although this initial mask-making strategy wasn’t very practical, I recognized the importance of having not only a mask, but one that would fit such that it properly served its purpose: to preserve my health. By fashioning a collaborative, autoethnographic approach to understanding craftivism during the 2020 coronavirus crisis, from a Black scholar doing disparities and equity focused health communication work and a white scholar engaging activist rhetorics and digital media equity scholarship, our joint recognition of economic and infrastructural privilege offered understanding of how forms of pattern design (techne) and cultural community infrastructure influenced our maker agencies and constraints, privileges and oppressions, of ourselves and people within our communities. Reflecting on our immersive mask-making experiences, we recognized a value of creating alternative economic structures; yet also unmasked significant racial discrepancies within craftivist communities by detailing how alternative economic agency required cultural historic materiality and knowledge, time to create and revise, networked access, and risk. Here, we offer insight into how a crisis revealed systemic biases as agency to reorient ourselves toward anti-racist processes and practices. Through our mutual exigency to craft masks, we witnessed how craftivism fostered white capitalist privilege within networked communities, prompting ethical questions about how alternative economic cultures buttress white privilege and supremacy and reimaginings of equitable possibilities for more just societies.